EFEKTIVITAS LAYANAN PENGUASAAN KONTEN UNTUK MENGURANGI PERILAKU PHUBBING SISWA DI SMA NEGERI 4 KOTA JAMBI - Syaharani Putri, Adhelia; Amanah, Siti; Andi Yaksa, Rully (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Phubbing is the behavior of ignoring others in face-to-face interactions due to being focused on smartphones, which negatively impacts interpersonal communication, social relationships, and students' learning process. This study aims to test the effectiveness of content mastery services in reducing phubbing behavior among grade X students of SMA Negeri 4 Kota Jambi. A quantitative approach with a quasi-experimental method and a nonequivalent control group design was used, involving 34 students consisting of 17 students in the experimental group and 17 students in the control group, selected through purposive sampling. The research instrument was a phubbing behavior scale based on indicators of phone obsession and communication disturbance. Data were analyzed using Paired Sample t-test, Independent Sample t-test, and Cohen's d effect size. Results showed a decrease in the phubbing score of the experimental group from 90.35 to 72.00, while the control group decreased from 87.82 to 77.12. The significance value for both tests was 0.000 (p < 0.05) with a Cohen's d effect size of 1.41, classified as a large effect. It was concluded that content mastery services are effective in reducing phubbing behavior and can be used as an alternative guidance and counseling service to improve students' interpersonal communication quality.